1981
DOI: 10.1002/jsfa.2740321219
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of champagne volatiles during ageing

Abstract: The change in aroma composition during champagneageing on yeast has been studied by gas chromatography and coupled gas chromatography-mass spectrometry of the volatiles trapped on Porapak Q. Analyses were made on samples kept on yeasts for 2 months and I , 2, 3,4, 5, 6 , 7 and 16 years, respectively. A rapid increase in the level of volatiles was noted in the first period. As ageing proceeded a slow decrease of nerolidol, isoamyl butyrate and hexyl acetate level was observed while vitispirane and benzaldehyde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
2
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 7 publications
2
17
2
2
Order By: Relevance
“…During wine ageing, benzaldehyde formation has been attributed to phenylalanine oxidation (Loyaux et al, 1981), while other authors have reported its origin from amygdalin (Nykänen & Suomalainen, 1982). The concentration of benzaldehyde in a range of white wines oxidised for one week was found to be between 20 and 313 µg/L , and the compound correlated well with the term "liquor" .…”
Section: Aldehydesmentioning
confidence: 99%
“…During wine ageing, benzaldehyde formation has been attributed to phenylalanine oxidation (Loyaux et al, 1981), while other authors have reported its origin from amygdalin (Nykänen & Suomalainen, 1982). The concentration of benzaldehyde in a range of white wines oxidised for one week was found to be between 20 and 313 µg/L , and the compound correlated well with the term "liquor" .…”
Section: Aldehydesmentioning
confidence: 99%
“…Cette phase aqueuse est saturée avec du chlorure de sodium puis amenée à pH 9,5 avec de l'hydrogénocarbonate de sodium puis extraite par du Forane 11 distillé (1 fois 10 ml et 4 fois 7 ml). Après avoir ajouté à l'extrait organique, 2 f-LI d'une solution de dodécane à 1 % dans du dichlorométhane, comme standard interne, cet extrait est concentré à 30 f-LIavec des colonnes de Dufton de différentes tailles (LOYAUX et al, 1981). (LEFORT, 1980 ;GUICHARD et ISSANCHOU, 1983 (LEBART et MORINEAU, 1985).…”
Section: B Extraction Et Concentration Des Constituants Volatilsunclassified
“…The volatile compounds (4,5-dimethyltetrahydrofuran-2,3-dione, 5-ethoxybutyrolactone, benzaldehyde, and diacetyl) previously identified in old Champagne wines (3)(4) did not account for the empyreumatic nuances in their bouquet.…”
Section: Introductionmentioning
confidence: 96%